FRI0113 Switching to anti-il-6 biologics after anti-tnf therapy in children with jia. (12th June 2018) - Alexeeva, E.; Dvoryakovskaya, T.; Soloshenko, M.; Denisova, R.; Isaeva, K.; Mamutova, A.; Gladkikh, V.; Moskalev, A.
Abstract : Background: Development of biologics gives rise to novel classes of drugs, offering more options for treating children with primary or secondary failure of anti-TNF therapy. However, the question of whether or not previous exposure to biologic therapy and the number of previously administered biologics influence the efficacy of current treatment still needs to be solved. Objectives: To compare tocilizumab efficacy in biologics-naïve and biologics-switched patients with JIA. Methods: Comparative analysis involved patients who had initiated TOC treatment at the National Medical Research Centre of Children's Health (Moscow) depending on previous history of biologics therapy. Treatment efficacy was evaluated according to the dynamics of clinical and laboratory signs using the ACRPedi criteria. The Wallace criteria were used to evaluate whether or not remission had been achieved. Results: Thirty-two patients were biologics-naïve and 43 patients switched to TOC were previously treated with ETA (n=10), ADA (n=34), certolizumab (n=2), and infliximab (n=1). Children in the biologics-naïve group differed from the switchers in a number of important baseline parameters: shorter disease duration (2.13 [1.25:5.34] and 7.42 [3:10.75] years, respectively; p<0.001) and lower arthritis severity indices (the number of joints affected, the CHAQ and JADAS scores). Therapy with TOC in children was found very effective. The CHAQ and JADAS disease activity scores, the CRP and ESR laboratory values, morning stiffness duration, and the VAS score (assessed by both patient and physician), and the number of affected joints (swollen or painful joints, joints with the limited range of motion and with active arthritis) significantly decreased after 4 week therapy in all patients (p<0.01). The percentages of biologics-naïve patients and switchers who achieved ACR90 after the first 12 months of therapy were 31.25% and 25.6%, respectively (p=0.613). A smaller percentage of children achieved stable remission: 4.65% of switchers and 6.25% of biologics-naïve patients (p>0.999). Conclusions: Tocilizumab therapy is highly efficient both as the first and subsequent biologic agent. Children with history of therapy with at least one biologic agent have lower chances for achieving remission during the first 12 months of therapy. However, this difference is most likely caused by the longer and more severe arthritis course in children allocated to the group of biologics-switched patients compared to biologics-naïve ones. Further matched large-cohort study is needed to identify predictors of response to therapy. Disclosure of Interest: E. Alexeeva: None declared, T. Dvoryakovskaya Grant/research support from: Roche, Pfizer, M. Soloshenko: None declared, R. Denisova: None declared, K. Isaeva: None declared, A. Mamutova: None declared, V. Gladkikh: None declared, A. Moskalev: None declared